Biosecurity risk and impact calculator - Chandwani, Somil (Kansas State University, 2008)
"BRIC" is a web survey application that can provide feedback to the feedyard managers regarding the different types of risk involved in their feedyards. By answering a set of basic questions in the survey, the application generates three categories of reports for the managers which provide them with measures to improve the existing condition of their feedyard. These dynamically generated reports can help to decrease the risk of introduction of some disease or its impact once it is introduced in a feedyard. The survey can be beneficial to collect data from various feedyards through the internet. This collected data can be used to make some interesting analysis and beneficial conclusions in this field of research.
Keywords: BIOSECURITY RISK; BRIC; Computer Science (0984)